Management skills in IT shaping your career - Atkins, Jooli; Mitchell, Simon; Gamester, Jean; Flood, Gary; McKay, Dave; Apte, Amitabh; Chapman, Rob (British Informatics Society, 2011)
This collection of articles and blog posts by IT industry experts explores the challenges IT professionals face when moving from a technical into a managerial role. The authors look at the skills required to scale the career ladder, the opportunities for training and development and how to progress from a first job in IT to CIO.
Includes bibliographical references. - Print version record
Keywords: Marketing -- Management; Marketing; Gestion; BUSINESS & ECONOMICS; Distribution; BUSINESS & ECONOMICS; Marketing; General; Marketing; Management; Business